Relationship between three commonly used non‐invasive fibrosis biomarkers and improvement in fibrosis stage in patients with non‐alcoholic steatohepatitis. (21st February 2019) - Chalasani, Naga; Abdelmalek, Manal F.; Loomba, Rohit; Kowdley, Kris V.; McCullough, Arthur J.; Dasarathy, Srinivasan; Neuschwander‐Tetri, Brent A.; Terrault, Norah; Ferguson, Beatrice; Shringarpure, Reshma; Shapiro, David; Sanyal, Arun J.
Abstract: Background & Aims: Non‐invasive biomarkers are needed for monitoring changes in liver histology in patients with non‐alcoholic steatohepatitis (NASH). Obeticholic acid (OCA) was shown to improve fibrosis in patients with NASH in the FLINT trial; a post hoc analysis of these data was performed to determine the relationship between 3 non‐invasive fibrosis markers and liver fibrosis improvement. Methods: In the Phase 2b FLINT trial, patients were randomised (1:1) to receive 25 mg OCA or placebo once daily for 72 weeks. Aspartate aminotransferase:platelet ratio index (APRI), fibrosis‐4 (FIB‐4) index and non‐alcoholic fatty liver disease fibrosis score (NFS) were evaluated in serum at baseline and weeks 24, 48, 72 and 96. Liver biopsies were obtained at baseline and 72 weeks. Results: In patients with fibrosis improvement at week 24, scores were reduced by a median of 34% for APRI, 10% for FIB‐4 and 4% for NFS. Reductions in APRI ( P = 0.015) and FIB‐4 ( P = 0.036), but not NFS ( P = 0.201) at week 24, significantly correlated with ≥1‐stage improvement in histologic fibrosis at week 72. Reductions in APRI at week 72 were significantly correlated with fibrosis improvement at week 72 ( P = 0.012). Patients receiving OCA had significant reductions in all markers compared with patients receiving placebo at week 72 [APRI and FIB‐4 ( P < 0.0001); NFS ( P < 0.05)]. Conclusions: Readily available non‐invasive markers may predict improvement in liver fibrosis in patients with NASH. Upon external confirmation and further refinement in larger populations, these markers may serve as surrogate endpoints in NASH clinical trials. Abstract : See Editorial on Page812